3D printing of carbon fiber-filled conductive silicon rubber. (15th March 2018) - Huang, Pei; Xia, Zhidong; Cui, Song
Abstract: Conductive silicon rubbers (CSRs) are potential candidates for strain sensor application owing to their specific electrical response and superior mechanical flexibility. In this work, carbon fiber-filled CSRs were printed by an extrusion device. Thixotropic agent was added to modify mobility and viscosity of the liquid CSR. It was found that the CSR with 5 wt% thixotropic agent addition exhibited better shape-retention. Fibers in matrix were observed to be oriented in the printing direction resulting in an anisotropic electrical and mechanical behavior. The printed CSRs showed better electrical and mechanical properties along the orientation direction of fibers. In particular, the volume resistivity at the orientation direction was 6.8 times lower than that at perpendicular direction. Higher tensile strength, larger elongation at break, and higher Young's modulus were found along the orientation direction when the printed CSRs were stretched, where a large number of fibers were pulled out and visible holes remained at the fractured surface. Electrical responses of the CSRs under various loadings, including stretching, compressing, bending, twisting and cyclic folding, were closely related with deformations of the CSRs. Sandwich strain sensors were finally fabricated to verify a practical application as motion sensor of the printed CSRs. Graphical abstract: Image 1 Highlights: Carbon fiber-filled conductive silicon rubbers were printed by an extrusion device. Oriented fibers in matrix resulted in an anisotropic electrical and mechanical behavior. The printed composites exhibited a good shape-retention with the addition of thixotropic agent. Electrical responses of the printed composites were closely related with various deformations. Sandwich strain sensors were successfully fabricated with the conductive silicon rubber.